Tracking the Ghosts of the Himalayas: Snow Leopard Conservation Insights From Satellite Collar Data - Pratistha Shrestha; Dayaram Pandey; Pemba Sherpa; Prakash Shah; Dipesh Kumar Sharma (Ecology and Evolution)
ABSTRACT This study presents the first movement analysis of snow leopards (Panthera uncia) using satellite telemetry data, focusing on the northeastern Himalayas of Nepal. By examining GPS‐based satellite collar data between 2013 and 2017 from five collared snow leopards (effectively three individuals), the research uncovered distinct movement patterns, activity budgeting and home range utilisation from one adult male and two sub adult females. Hidden Markov models (HMMs) revealed three behavioural states based on the movement patterns—slow (indicative of resting), moderate and fast (associated with travelling) and demonstrated that the time of day influenced their behavioural state. While adult males exhibited behaviour focused on moderately active states, juvenile females presented behaviour focused on highly active states. Home ranges, estimated over a 5–21 month tracking period, were larger than those observed in previously studied snow leopards and included crossings of international boundaries from Nepal into China and India. These relatively large home ranges may be attributed to the rugged terrain and scarce resources within the study area. This research suggested that movement patterns and home range sizes might differ between male and female snow leopards, which may indicate different ecological needs and resource‐use techniques. Furthermore, this study provides reliable information on snow leopards from the telemetry data and links it to conservation implications in northeastern Nepal to ensure their long‐term survival, promote coexistence and foster cross‐border collaboration.